VL2: A Scalable and Flexible Data Center Network - Greenberg, Albert; Hamilton, James R.; Jain, Navendu; Kandula, Srikanth; Kim, Changhoon; Lahiri, Parantap; Maltz, Dave; Patel, Parveen; Sengupta, Sudipta (SIGCOMM, 2009)
To be agile and cost effective, data centers should allow dynamic resource allocation across large server pools. In particular, the data center network should enable any server to be assigned to any service. To meet these goals, we present VL2, a practical network architecture that scales to support huge data centers with uniform high capacity between servers, performance isolation between services, and Ethernet layer-2 semantics. VL2 uses (1) flat addressing to allow service instances to be placed anywhere in the network, (2) Valiant Load Balancing to spread traffic uniformly across network paths, and (3) end-system based address resolution to scale to large server pools, without introducing complexity to the network control plane. VL2’s design is driven by detailed measurements of traffic and fault data from a large operational cloud service provider. VL2’s implementation leverages proven network technologies, already available at low cost in high-speed hardware implementations, to build a scalable and reliable network architecture. As a result, VL2 networks can be deployed today, and we have built a working prototype. We evaluate the merits of the VL2 design using measurement, analysis, and experiments. Our VL2 prototype shuffles 2.7 TB of data among 75 servers in 395 seconds – sustaining a rate that is 94% of the maximum possible. Invited paper in Research Highlights section of the newly re-formatted Communications of the ACM (CACM).
Recognized as one of "the most important research results published in CS in recent years".